SIFAT PAPAN WOL KAYU SEBELAS JENIS KAYU DARI SUMATRA SELATAN DAN JAWA BARAT - I M Sulastiningsih; Rozak Memed; Paribroto Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The results of laboratory test of wood-wool board properties manufactured from 11 individual wood species obtained from South Sumatra and West Java are reported in this paper. The tests comprising board density, moisture content, thickness reduction due to compression and bending strength.The study reveals that average yield of wood-wool is 315 kg per cubic meter of log input. The physical and mechanical properties of wood-wool board from five wood species. mineralized with CaCl2 solution were in conformity with the DIN 11.01 standard. However, only four wood species mineralized with Ca(OH)2 suspension met the standard requirements.